THE SIGNIFICANCE OF CLINICAL PROTOCOLS IN SURGICAL DISCIPLINES (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2014)
In the current article we aim to describe and show the significance of evidence-based medicine (EBM) in surgical disciplines, as this is expressed through the application of clinical protocols and clinical indicators of quality and outcome. We also probe the questions of clinical protocols assisting in hospital management, and moreover of the political and political-ethical issues for the implementation of clinical protocols in the pursuit of better hospital management. Clinical protocols are guidelines with broader scientific acceptance, helping physicians, surgeons and health staff in general, to perform a procedure or combination of procedures with the best possible results at the lowest possible cost. Clinical indicators are implemented in order to assess the achieved results; such indicators are in-hospital mortality, frequency of adverse events such as stroke or venous thromboembolism, duration of hospitalization, incidence of reoperation, incidence of re-admittance etc. The article also includes, for reasons of better understanding, two examples of clinical protocols (coronary artery surgery and total hip arthroplasty).